AKAR TEOLOGIS KETIMPANGAN GENDER: Pemikiran Feminisme Riffat Hassan - Maftukhatusolikhah Maftukhatusolikhah (Millah: Journal of Religious Studies, 2002)
The consciousness of gender discrimination which causes discrimination treatment toward man and women, emerges feminism movement around the world, including the Islamic World. It can be proven by emergence of some Muslims who involve infeminism movement in Muslim countries. One of them is Riffat Hassan, theologian-feminist who is born in Lahore, Pakistan. Feministic thought of Riffat Hassan is a formulation from complex situation, which is influenced by elements of culture, society, politic, and her education. The interesting thing of Riffat Hassan's thought is her effort to search theological doctrine (Qur 'an and Hadits). According to Riffat, some Muslim interpreters, who are men intentionally misinterpret it. Therefore, Riffat devotes her ability to reinterpret the theological doctrines. Even, she tries to criticize authenticity and authority of Hadith, which is used by the classical interpreters as basic of their opinion. This study will discus and criticize thought of Riffat Hassan who tries to explain eternal prophetic message of Qur'an, especially verses pertaining to women in the context of time and space, it will produce new reading of Qur'an, infeminism perspective.